Найдите значение выражения: (pq/p+q) * (q/p-p/q)   при p=3-2√2, q=-2√2

Найдите значение выражения:  (pq/p+q) * (q/p-p/q)   при p=3-2√2, q=-2√2
Гость
Ответ(ы) на вопрос:
Гость
[latex]( \frac{pq}{p+q})*( \frac{q}{p}- \frac{p}{q})=(\frac{pq}{p+q})*(\frac{qp-p^{2}}{qp})= \\ \\ \frac{pq(qp-p^{2})}{qp(p+q)}= \frac{p^{2}q(q-p)}{qp(p+q)};\\\\\\ \frac{(3-2 \sqrt{2})^{2}*(-2 \sqrt{2})(-2 \sqrt{2}+3-2 \sqrt{2})}{(-2 \sqrt{2})*(3-2 \sqrt{2})(3-2 \sqrt{2}-2 \sqrt{2})}= \frac{(3-2 \sqrt{2})(3-4 \sqrt{2})}{(3-4 \sqrt{2})}=3-2 \sqrt{2}[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы